2015
DOI: 10.15406/mojor.2015.02.00068
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Low Level Laser Therapy (LLLT) For Musculoskeletal Pain

Abstract: Pain is the most common reason for physician consultation in the United States. One out of three Americans is affected by chronic pain annually. The number one reason for missed work or school days is musculoskeletal pain. Currently accepted therapies consist of non-steroidal anti-inflammatory drugs, steroid injections, opiate pain medications and surgery, each of which carries their own specific risk profiles. What is needed are effective treatments for pain which have an acceptably low risk-profile. For over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
159
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(183 citation statements)
references
References 86 publications
0
159
0
8
Order By: Relevance
“…[1][2][3] Moreover, laser therapy can stimulate repairs to damaged tissues and peripheral nerves leading to neurological regeneration. 1,4,5 Low-power laser (light) therapy (power ≤ 500 mW) can be used to decrease acute and chronic pain, induce recovery of damaged nerves, enhance peripheral circulation and metabolism, and reduce joint inflammation. 2,5,6 The effects of low-power laser therapy are photochemical not thermal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Moreover, laser therapy can stimulate repairs to damaged tissues and peripheral nerves leading to neurological regeneration. 1,4,5 Low-power laser (light) therapy (power ≤ 500 mW) can be used to decrease acute and chronic pain, induce recovery of damaged nerves, enhance peripheral circulation and metabolism, and reduce joint inflammation. 2,5,6 The effects of low-power laser therapy are photochemical not thermal.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 Low-power laser (light) therapy (power ≤ 500 mW) can be used to decrease acute and chronic pain, induce recovery of damaged nerves, enhance peripheral circulation and metabolism, and reduce joint inflammation. 2,5,6 The effects of low-power laser therapy are photochemical not thermal. In a recent review, Cotler et al concluded that low-power laser therapy is a new cost-effective therapy for musculoskeletal pain, which improves the quality of life and reduces financial strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, LLL has a biostimulatory action on wound healing acceleration which takes place by photo‐biostimulation of mitochondria, activating signaling pathways, leading to the increase of transcription factors and subsequent growth factors production. Furthermore, LLL has been proved to enhance and stimulate cell proliferation …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LLL has been proved to enhance and stimulate cell proliferation. 50 The suggested regenerative approach provided the patient with better soft tissue healing, bone regeneration, and aesthetics. We believe that the combination of tissue engineering and laser technologies helped to improve the clinical outcomes of the case.…”
Section: Discussionmentioning
confidence: 99%